An enforced loop-out knowledge flow facilitates industry competition: Learning from the pharmaceutical and genetically modified seed industries. (January 2019) - Chang, Ching-Wen; Yamanaka, Takayuki; Kano, Shingo
Abstract: Maintaining industry diversity and avoiding oligopolistic market structures are important issues for governments. To facilitate launching generic products, the US government has established special policies for the country's pharmaceutical industry, namely, the Orange Book, the Bolar Amendment, and the ANDA procedure, which this study regards as an essential policy package. The three policies are functionally generalized and combined with a corporate knowledge cycle to construct a "policy-enforced loop-out knowledge flow model, " which fuses corporate knowledge management and policy intervention, to explain how the policies have facilitated knowledge utilization. This model explains the synergy effect of these policies as a combination of knowledge confirmation, fast knowledge utilization, and reduced additional knowledge from the knowledge perspective. The model is applied to the oligopolistic genetically modified (GM) seed industry, in which no generic GM seeds have appeared in the market after main patents expiry. We find that policies to facilitate the loop-out knowledge flow are lacking in the GM seed industry and that a policy package could be used to solve the industry's oligopoly. Product patent linkage monitoring is especially key for governments, and its disclosure could facilitate the knowledge loop-out from the originator's knowledge cycle to other competitors in highly concentrated markets. Highlights: Extracts the three policies to maintain competitive environment from the US pharmaceutical industry. Product-Patent Linkage (PPL) Disclosure, R&D Freedom, and Abbreviated Regulatory Path can facilitate the generic product launching into the market. An enforced loop-out knowledge flow model constructed from three policies and used to analyze GM seed industry. Without the Product-Patent Linkage Disclosure, new enters are hard to join GM seed industry. The model will provide implications for making competitive environment of oligopolistic industries.